Students’ Ability in Proving Pythagorean Theorem through Discovery Learning Model Using Geogebra Software - Fathiya Salsabila; Rahmah Johar; Susanti Panca Wahyuni (Proceedings of AICS - Social Sciences, 2017)
Learning math is like training logical thinking, intelligence, focus and also systematics. One of the most important materials in math is Pythagorean Theorem. It is used in many aspects of life and helps us to solve daily problems. However, many students still cannot use it we even they have learned it. The aim of this study research is to describe the students’ learning ability process through discovery learning model using GeoGebrasoftware on Pythagorean Theorem. The subjects of this study were the students of SMP Negeri 6 Banda Aceh 29 students of grade VIII-8. The data which was analyzed is formed tasks which were done in groups and video analysis. The results of study showed that the students are able to accomplish worksheet through GeoGebra assistedand all of them are able to take conclusion symbolically yet not by using their own words. The first group was failed to count third area but they succeeded on counting other areas which lead them to the right conclusion. The second group’s fault was on naming a square particularly on its third area however they were better taking the right conclusion. The obstacles of learning process were (1) limitation of time, (2) only some students practice using GeoGebra software, (3) laptops used were slow and not responding, (4) even the student did not understand the beginning explanations.  Keywords:     learning, discovery learning model, GeoGebra software, Pythagorean Theorem.